The Effect Of Electronic Money And Bi-Rate On Inflation In Indonesia - Sinta Yulyanti; Rafli Ismail (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the effect of electronic money and the BI-Rate on inflation in Indonesia. The background of this research is the increasing use of electronic money in economic transactions by society, as well as the role of the BI-Rate as a monetary policy instrument used by Bank Indonesia to control inflation. This study employs a quantitative method with an Error Correction Model (ECM) approach to examine the long-term and short-term relationships among the variables. The data used in this research are secondary annual data from 2009 to 2023, obtained from Bank Indonesia and the Central Statistics Agency. The results indicate that, partially, electronic money affects inflation but not significantly, while the BI-Rate has a positive and significant effect on inflation. Simultaneously, both variables significantly influence inflation in Indonesia. These findings imply that although electronic money facilitates transactions, its impact on inflation control remains limited, whereas the BI-Rate continues to serve as the main instrument in controlling national inflation.